(3QjGV GdeSGFds - (3GdWHGWHGFj, GdcGXej, GdMGFQj, GdCUHgGfj, Ydj Hf eMeO Ydj Hf CHj GdeYGdj, J (B1231 (3gs ((3MSjf Hf Ydj GdHMQGfjs)
(3ChdgG (B:s
(3HSe Gddg (B... (3cJGH GdehGQjK , hgh CYe ef GdaQGFV eWdbG Ef CQjO HgG GdeaQhV HGdJaUjd hEf CQjO HgG eG jYe GdELeGd cEQK Chdj GdCQMGe agh HeYfGg hef Ke cGf GdJYHjQ HeG gfG Chdi ef GdJYHjQ HGdaQGFV(B...s
(3BNQgG (B:s
...(3Ydi eG bOefGg ceG YedJ aj aQjVI GdKGfj eY GdChd hgcPG dh eGJ QGHY hNGeS heG RGO hcYed hGMO hLejYG JbOe ajeG SHb ef GdEaQGOGJ gfG CjVG hGdMeO ddg bO Je cJGH GdejQGKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\ 17s
(3GdPQjYI (B11\1999s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis